GRAMMATICAL ERRORS IN LITERATURE AND PHILOSOPHY STUDENT ESSAYS AT PANCA MARGA UNIVERSITY, PROBOLINGGO: English - Siti Masluha (Journal of English Development, 2021)
A Abstract: Understanding grammatical in making writing and composition being crucial for the learners. It takes important rule for making good writing and composition so that the readers can comprehend the benefit of it. Some grammatical errors have been found in the writing of English Letter and Philosophy students. Errors in grammar automatically cause misunderstanding and misinterpretation. Through descriptive qualitative method employed in this study it revealed that the writer’s prior knowledge o grammatical rules in Indonesia language had caused problems. Ten essays were taken as the main source of the data. The essays were taken from the final test of Writing II that was held on January, 15th 2018. From the findings it can be conclude that the writers have big deals in giving ending -s/-es in present form, giving the article, determining correct preposition, choosing appropriate words, forming passive, adding suffix, and giving final ‘s in possessive and determining plural and singular. All those problems were suspected as the impact of writers’ prior knowledge on the source language. The leaners were still in adaptation on using grammatical rules in the target language, English in this case. The formulation of some phrases and sentences were often come in source language rules. Finally, the result of this research is expected to be able to give meaningful contribution to students of English Letter and Philosophy and all the readers as well.